Optimization and Effect of Water Hardness for the Production of Slightly Acidic Electrolyzed Water on Sanitization Efficacy - Yan, Pianpian; Jo, Hyeon-yeong; Chelliah, Ramachandran; Jo, Kyoung hee; Woo, Nam Chan; Wook, Min Seung; Oh, Deog Hwan (Frontiers in Microbiology, 2022)
Slightly acidic electrolyzed water (SAEW) has been recently proposed as a novel promising sanitizer and cleaner in the agricultural and food industries. However, several factors, including water hardness, were considered to strongly affect the physical properties and sanitization efficacy of SAEW. To study the effect of water hardness on the SAEW production, we evaluated the production properties and sanitization effect of SAEW, which was generated from water source in 16 representatively geographical locations of South Korea. The results showed that the hardness of water sources from Kangwon-do, Jeollanam-do and Daegu was 22 – 41 ppm, Busan, Gyeongnam-do, Gwangju Bukgu was 80-443 ppm and that from other 7 locations was 41-79 ppm. The SAEW, produced from water hardness below 50 ppm and above 80 ppm was beyond the accepted pH range (5.0-6.5). Notably, high hardness water (above 80 ppm) containing 5% HCl could be used to produce the SAEW with accepted pH. The SAEW, generated from low hardness water with additions of 2% HCl and 2 M NaCl at 7 A showed accepted pH and higher germicidal effect. Furthermore, SAEW with the ACC of 27-41 mg/ L for 1 minute was sufficient to completely inactivate non-spore forming foodborne pathogens. Sanitization efficacy was not markedly affected by storage conditions for SAEW at 40 ppm. Our results demonstrated that the degree of water hardness is an important factor in the production of SAEW, which would provide a foundation for commercial application of SAEW.